Antimicrobial use for influenza-like illnesses in Nha Trang, Vietnam: a cross-sectional study - Philippe Beutels; Shinya Tsuzuki; Michiko Toizumi; Hien-Anh Thi Nguyen; Hien Minh Vo; Hoang Huy Le; Duc Anh Dang; Lay Myint Yoshida (BMJ Open)
Objectives This study aimed to investigate the characteristics and management of influenza-like illnesses (ILIs) in the outpatient and inpatient settings in Vietnam.Design A cross-sectional, observational study.Setting and participants We conducted a questionnaire survey of 407 individuals with ILI symptoms who presented to public community health centres and the paediatric ward of a public hospital in the city of Nha Trang, Khanh Hoa Province, Vietnam, from December 2022 to March 2023.Interventions Not applicable.Primary and secondary outcome measures No primary and secondary outcomes were pre-specified because this study was an explanatory study. The basic characteristics of the participants are presented using descriptive statistics. We conducted multivariable logistic regression analysis to examine the factors associated with the prescription of antibiotics to outpatients with ILIs.Results A total of 198 outpatients and 200 inpatients were enrolled in the study. Most inpatients were children under 5 years of age and experienced longer illness durations and higher costs, with almost all patients receiving antibiotics. The rate of antimicrobial prescription for ILIs was 79.3% for outpatients and 99.5% for inpatients. The median health-related quality of life score of participants aged ≥18 years during illness was 0.796 (IQR 0.674–0.922). Logistic regression analysis indicated a negative association between a definite diagnosis of viral infection by rapid diagnostic test and outpatient antibiotic prescription (OR: 0.20, p=0.006).Conclusions This study underscores the widespread inappropriate antimicrobial use for ILIs in a community in Vietnam, which contributes to an avoidable economic and health burden. The results of this study suggest that implementing diagnostic tools may support antimicrobial stewardship efforts.